The Trouble with Textbooks Distorting History and Religion. - Tobin, Gary A.; Ybarra, Dennis R. (Lanham : Lexington Books, 2008)
Our elementary, middle, and high school teaching about Jews, Judaism, and Israel is driven by textbook misstatements about Jewish theology, social structure, and the history of Israel that comprise an unsavory picture of Jews and Israel. This book will be an extremely valuable reference tool for educators and members of the public interested in religion and the Middle East.
Appendix A Textbooks Reviewed by Publisher Parent CompanyAppendix B Imprints of Major Textbook Publishing Corporations; Appendix C Textbook Usage Survey: Extent of Usage by Publisher Parent Company; Appendix D Outline of the Arab Narrative; Notes; Index; About the Authors.
Description based on print version record.
Keywords: Israel -- History -- Study and teaching -- United States; Jews -- History -- Study and teaching -- United States; Judaism -- Study and teaching -- United States; Public schools -- United States; Textbook bias -- United States; Textbooks -- Censorship -- United States; Textbook bias -- United States; Jews -- History -- Study and teaching -- United States; Judaism -- Study and teaching -- United States; Public schools -- United States; HISTORY / World; Electronic books